Comparative study of the efficacy of oral and intravenous maternal hydration in the management of third trimester oligohydramnios and it’s effect on maternal and foetal outcome - Khajotia, Santosh; Naraniya, Deepak; Meena, Shubha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Amniotic fluid is derived from maternal plasma in very early pregnancy by the 10th week of pregnancy. It forms an aquatic pond inside the amniotic cavity surrounding the fetus. It helps in fetal development. Aim of this study was to determine the impact of hydration therapy in patients complicated by oligohydramnios. Methods: This was a prospective randomized clinical trial conducted on 200 women. Results: Mean AFI in Group I was 4.47±0.90 cm before hydration therapy and 7.16±1.57 cm after hydration therapy with elevation by 60.18%, similarly mean AFI in Group II was 4.52±0.83 cm before hydration therapy and 7.48±1.56 cm after hydration therapy with elevation by 65.48%. However, on comparing the two groups elevations in mean AFI was found statistically insignificant (p >0.05). Conclusions: Oral hydration is non-invasive, low costing, does not exhaust the resource, convenient to the women with minimum side effects and can be done at home.